Effects of Subjective Memory Complaints (SMCs) and Social Capital on Self-Rated Health (SRH) in a Semirural Malaysian Population. (10th April 2019) - Yap, Kwong Hsia; Mohan, Devi; Stephan, Blossom C. M.; Warren, Narelle; Allotey, Pascale; Reidpath, Daniel D.
Abstract : Subjective memory complaints (SMCs) and social capital were known to be related to self-rated health (SRH). Despite this, no studies have examined the potential interaction of SMC and social capital on SRH. Using data from a cross-sectional health survey of men and women aged 56 years and above ( n = 6, 421), we examined how SMCs and social capital explained SRH in a population of community-dwelling older adults in a semirural area in Malaysia. We also evaluated whether SRH's relationship with SMCs is moderated by social capital. The association of SMC and social capital with poor SRH was investigated using multivariable logistic regression. Social capital (OR = 0.86, 95% CI = 0.82–0.89), mild SMC (OR = 1.70, 95% CI = 1.50–1.94), and moderate SMC (OR = 1.90, 95% CI = 1.63–2.20) were found to be associated with poor SRH after adjustment for sociodemographic factors and depression in the initial regression model. SMC was found to have partial interaction effects with social capital which was included in the subsequent regression model. Unlike individuals with no SMC and mild SMC, those who reported moderate SMC did not show decreasing probabilities of poor SRH despite increasing levels of social capital. Nevertheless, this analysis suggests that social capital and SMC are independent predictors of poor SRH. Further research needs to be targeted at improving the understanding on how social capital and SMC moderate and interact with the perception of health in older adults.